Mood effects of blood flow restriction resistance exercise among basketball players - Silva, J. C. G.; Aniceto, R. R.; Oliota-Ribeiro, L. S.; Neto, G. R.; Leandro, L. S.; Cirilo-Sousa, M. S. (Perceptual and Motor Skills, 2018)
This study compared the acute effects of resistance exercise with and without blood flow restriction (BFR) on basketball players` mood states. A total of 11 male basketball players (M age = 19.9, SD = 2.8 years; M height = 180.8, SD = 7.8 cm; M weight = 71.1, SD = 9.1 kg; M body mass index = 22.1, SD = 1.9 kg/m2) were randomly assigned to two experimental conditions: (a) low-load resistance exercise with BFR (LLRE + BFR) and high-load resistance exercise (HLRE) without BFR. We measured mood state with the Brunel Mood Scale before and after each session. There was a significant interaction effect such that there was increased fatigue over time with LLRE + BFR (p = .001, % = 169.2). Regarding total mood disorder, there were significant pre and postexercise differences between athletes exposed to both the LLRE + BFR and HLRE conditions (p = .048) and a decharacterization of the iceberg mood profile in the post-training LLRE + BFR condition. LLRE + BFR, compared to HLRE, promoted an acute negative effect on mood state, decharacterization of the iceberg profile, total mood disturbance, and increased participant fatigue, suggesting that this method of strength training should be avoided before sports competitions.